Comparative Analysis of Long-term Success Rates and Patient Satisfaction among Different Implant Placement Techniques for Implant-Supported Restorations: A Prospective Clinical Trial - Akash Mithran; Vishal B. Parmar; Malav Sheth; Mansi; Soumalya Banerjee; Minu Raju (Journal of Pharmacy and Bioallied Sciences)
Objective: This prospective clinical trial aimed to rigorously investigate and compare the long-term success rates of implant-supported restorations using various implant placement techniques, including conventional two-stage implant placement, immediate implant placement, and guided implant surgery. Methods: A total of 168 participants were randomly assigned to three groups. Comprehensive preoperative assessments, involving detailed medical and dental histories, thorough clinical examinations, and cone-beam computed tomography scans, were conducted. The implant placement techniques included conventional two-stage, immediate placement, and guided surgery. Primary outcomes included clinical and radiographic implant success, while secondary outcomes encompassed prosthetic success, complication rates, and patient-reported outcomes. Results: Baseline characteristics demonstrated no significant differences among the groups. Implant success rates at 6, 12, and 24 months were consistently high, with no statistically significant differences between conventional two-stage (96.4%, 94.0%, and 91.1%, respectively), immediate placement (94.7%, 92.1%, and 88.5%, respectively), and guided surgery (98.2%, 96.4%, and 93.8%, respectively) techniques (P > 0.05). Prosthetic complications, including crown misfit, abutment screw loosening, and esthetic issues, exhibited comparable rates across groups (P > 0.05). Patient satisfaction scores remained consistently high at 6, 12, and 24 months, with no statistically significant differences between conventional two-stage (8.2 ± 1.1, 8.5 ± 0.9, and 8.8 ± 0.8, respectively), immediate placement (8.4 ± 1.0, 8.8 ± 0.8, and 9.1 ± 0.7, respectively), and guided surgery (8.7 ± 0.9, 9.0 ± 0.7, and 9.3 ± 0.6, respectively) techniques (P > 0.05). Conclusion: This study provides robust evidence supporting the comparable success rates, low prosthetic complications, and high patient satisfaction associated with conventional two-stage, immediate placement, and guided surgery techniques for implant-supported restorations.